Sub-coercive field dynamic hysteresis in morphotropic phase boundary composition of Pb(Zr1/2Ti1/2)O3-Pb(Zn1/3Nb2/3)O3 ceramic and its scaling behavior - Wongdamnern N. (2014)
Sub-coercive field dynamic ferroelectric hysteresis of a morphotropic phase boundary composition of the PZT-PZN ceramic was investigated under influence of the compressive stress. The scaling relation of hysteresis area 〈 A 〉 against frequency f, field amplitude E0, and stress σ took a form of 〈 A - Aσ = 0 〉 ∝ f- 0.33 E03.75 σ0.32, which is not different significantly to that of other PZT-PZN compositions with pure tetragonal or rhombohedral structure, as well as to that of soft and hard PZT bulk ceramics. This study suggested that the domain structures, not ceramic compositions, played a key role in controlling dynamic hysteresis behavior of ferroelectric materials. © 2009 Elsevier B.V. All rights reserved.